2014
DOI: 10.5194/isprsarchives-xl-8-21-2014
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Difference Vegetation Water Content (ddVWC) of Advance Microwave Scanning Radiometer-Earth Observing System (AMSR-E) for assessment of crop water stress at regional level

Abstract: Advance Microwave Scanning Radiometer -Earth Observing System (AMSR-E) derived Vegetation Water Content (VWC) at predawn (01:30 LST, descending pass) and afternoon (13:30 LST; ascending pass) were used to assess crop water stress condition over the selected meteorological subdivisions of India. The temporal profile of Normalized Difference Vegetation Index (NDVI) was used to study the progression of crop growth. The Diurnal Difference Vegetation Water Content (ddVWC) was found to be sensitive to rainfall patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Steele-Dunne et al (2012) conducted a numerical sensitivity study using the Michigan Microwave Canopy Scattering Model and concluded that combinations of morning and evening passes of the Soil Moisture Active Passive (SMAP) could potentially be used to assess the soil moisture stress over densely vegetated areas. The diurnal differences of VWC of AMSR-E was found to have potential to monitor drought at regional level, but has limitation to be applied across different vegetation density (Chakraborty and Sesha Sai 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Steele-Dunne et al (2012) conducted a numerical sensitivity study using the Michigan Microwave Canopy Scattering Model and concluded that combinations of morning and evening passes of the Soil Moisture Active Passive (SMAP) could potentially be used to assess the soil moisture stress over densely vegetated areas. The diurnal differences of VWC of AMSR-E was found to have potential to monitor drought at regional level, but has limitation to be applied across different vegetation density (Chakraborty and Sesha Sai 2014).…”
Section: Introductionmentioning
confidence: 99%